2007
DOI: 10.1007/s00247-007-0427-z
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific induction of lymphatic malformations in a rat model for image-guided therapy

Abstract: This model represents a promising tool for translational development of image-guided interventions for lymphatic malformations. It may also serve as a model for the study of lymphangiogenesis and the development of anti-lymphangiogenic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…12,[15][16][17][18][19] Identification of specific lymphatic markers, such as LYVE-1, D2-40, podoplanin, VEGF-C, and VEGF-D, has advanced the characterization of lymphatic tissue. 6,[19][20][21][22][23][24][25][26] An animal model of lymphatic malformations, induced via intraperitoneal injection of Freund's incomplete adjuvant, may enable further studies on endovascular therapies for these lesions. 24 In contrast, intraperitoneal injection of Freund's incomplete adjuvant resulted in a vascularized oil granuloma rather than a lymphatic malformation.…”
Section: Lymphatic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[15][16][17][18][19] Identification of specific lymphatic markers, such as LYVE-1, D2-40, podoplanin, VEGF-C, and VEGF-D, has advanced the characterization of lymphatic tissue. 6,[19][20][21][22][23][24][25][26] An animal model of lymphatic malformations, induced via intraperitoneal injection of Freund's incomplete adjuvant, may enable further studies on endovascular therapies for these lesions. 24 In contrast, intraperitoneal injection of Freund's incomplete adjuvant resulted in a vascularized oil granuloma rather than a lymphatic malformation.…”
Section: Lymphatic Developmentmentioning
confidence: 99%
“…6,[19][20][21][22][23][24][25][26] An animal model of lymphatic malformations, induced via intraperitoneal injection of Freund's incomplete adjuvant, may enable further studies on endovascular therapies for these lesions. 24 In contrast, intraperitoneal injection of Freund's incomplete adjuvant resulted in a vascularized oil granuloma rather than a lymphatic malformation. 25 Histologically, lymphatic malformations are thinwalled fluid-filled cysts with surrounding connective tissue-containing stroma.…”
Section: Lymphatic Developmentmentioning
confidence: 99%
“…Currently, a universally accepted model for human LM is not available for experimental investigation. In a recent study, Short and colleagues23 reported an in vivo rat model of LM that was created using intraperitoneal injection of Incomplete Freund's Adjuvant. LM were detected in the abdomen and neck by ultrasound near 45 days postinduction.…”
Section: Discussionmentioning
confidence: 99%
“…LECs for cultures were also isolated from lymphangiomas, which are lesions induced by incomplete Freund's adjuvant injection into the peritoneal cavity of mice (40) or rats (41). Lymphatic vessels from this lesion are mechanically disrupted, and LEC is enzymatically isolated before seeding onto a 2-D substrate (42,43) or being embedded in a fibrin gel for 3-D cultures (44).…”
Section: Isolation Methodsmentioning
confidence: 99%